ANALISIS PENYEBAB ANAK PUTUS SEKOLAH PADA KASUS BROKEN HOME DI DESA UMBU RIRI KABUPATEN SUMBA TENGAH - Sailang, Maria Melinia; Mardani, Ambara Saraswati; Klau, Erni Raster (Education For All, 2024)
A broken home refers to a married couple encountering family issues that eventually result in the termination of their relationship through separation or divorce. This situation often negatively impacts the children, affecting their education. Therefore, this study aims to inv estigate the factors causing children to drop out of school in broken home cases. The methodology employed in this study is qualitative research with a case study approach to explore the phenomenon of school dropout due to broken home factors. The techniques used for data collection include observation, interviews, and documentation. The number of informants in this study is four indiv iduals aged 13-16 years who experienced broken home conditions, leading them to drop out of school. The research findings are categorized based on the broken home conditions experienced by the informants. The first condition is a broken family where the parents of the informant had separated. This situation adversely affected the informant, leading to the decision to quit school. The second condition involves the death of one or both parents, experienced by two informants, which rendered them powerless to continue their education, resulting in their decision to drop out of school. The third condition involves neglect, experienced by one informant whose parents had divorced, leav ing the informant uncared for and ultimately causing them to drop out of school.